Magnetoelectric coupling in Tb0.3Dy0.7Fe2/Pt/PbZr0.56Ti0.44O3 thin films deposited on Pt/TiO2/SiO2/Si substrate - Cibert, C.; Zhu, J.; Poullain, G.; Bouregba, R.; More-Chevalier, J.; Pautrat, A. (Applied physics letters, 2013)
Tb0.3Dy0.7Fe2/Pt/PbZr0.56Ti0.44O3 (Terfenol-D/Pt/PZT) thin films were sputtered on Pt/TiO2/SiO2/Si substrate. PZT and Terfenol-D layers were chosen for their large piezoelectric and magnetostrictive coefficients, respectively. 4%–5% magnetocapacitance has been measured on a Terfenol-D/Pt/PZT stack at room temperature. A magnetoelectric (ME) voltage coefficient of 150 mV/cm Oe was obtained at low dc magnetic field out of mechanical resonance. This work demonstrates the possibility to achieve ME effect in integrated devices involving Terfenol-D and PZT thin films providing that the diffusion, which may occur between both active layers is reduced using an intermediate layer.